Functional neuroanatomy of biological motion perception in humans - Vaina, Lucia M. (The National Academy of Sciences, 2001)
We used whole brain functional MRI to investigate the neural network specifically engaged in the recognition of “biological motion” defined by point-lights attached to the major joints and head of a human walker. To examine the specificity of brain regions responsive to biological motion, brain activations obtained during a “walker vs. non-walker” discrimination task were compared with those elicited by two other tasks: (i) non-rigid motion (NRM), involving the discrimination of overall motion direction in the same “point-lights” display, and (ii) face-gender discrimination, involving the discrimination of gender in briefly presented photographs of men and women. Brain activity specific to “biological motion” recognition arose in the lateral cerebellum and in a region in the lateral occipital cortex presumably corresponding to the area KO previously shown to be particularly sensitive to kinetic contours. Additional areas significantly activated during the biological motion recognition task involved both, dorsal and ventral extrastriate cortical regions. In the ventral regions both face-gender discrimination and biological motion recognition elicited activation in the lingual and fusiform gyri and in the Brodmann areas 22 and 38 in superior temporal sulcus (STS). Along the dorsal pathway, both biological motion recognition and non-rigid direction discrimination gave rise to strong responses in several known motion sensitive areas. These included Brodmann areas 19/37, the inferior (Brodmann Area 39), and superior parietal lobule (Brodmann Area 7). Thus, we conjecture that, whereas face (and form) stimuli activate primarily the ventral system and motion stimuli primarily the dorsal system, recognition of biological motion stimuli may activate both systems as well as their confluence in STS. This hypothesis is consistent with our findings in stroke patients, with unilateral brain lesions involving at least one of these areas, who, although correctly reporting the direction of the point-light walker, fail on the biological motion task.